(untitled) (South East Asia Journal of Public Health, 2018)
Urinary tract infection (UTI) is one of the most common bacterial infections seen in developing countries like Bangladesh. This study is, therefore, designed to determine the bacterial uropathogens and their antibiotic resistance pattern among patients with complaints of UTIs in Dhaka city. This study was carried out in the laboratory of the Department of Microbiology, Bangladesh Medical College, Dhaka, Bangladesh from January to June 2015. A total of 2541 urine samples were collected in sterile containers from suspected urinary tract infected cases. A specimen was considered positive for UTI if an organism was cultured at a concentration of ≥105CFU/ml or when an organism was cultured at a concentration of 104CFU/ml and >5 pus cells per high power field. Antimicrobial susceptibility testing of the isolated bacterial species was performed by disc diffusion method following the National Committee for Clinical laboratory Standards (NCCLS) guidelines. A total of 303 (11.92%) bacterial uropathogens were isolated from 2541 urine samples. Among the 303 isolates, majority of the isolates 197 (65.02%) were from females. Both the age groups up to 18 years and above 18 years the highest prevalence was found in females 34(11.22%) and 163 (53.79%) respectively. Most predominant organism was Escherichia coli 262(86.46%)followed by Pseudomonas 12(3.96%), Enterococci 12(3.96%), Klebsiella11(3.63%). Escherichiacoli showed very high resistance to amoxycillin 95.41%, cefradin 90.45%, nalidixic acid and Klebsiella to amoxycillin 90.90%, nitrofurantoin 90.90%. Again Pseudomonas was highly resistant to cefuroxime 100%, cefexime 100%and ceftriaxone 83.33%. Enterococci were found highly resistance to cefexime 91.66%, cloxacillin 83.33%, and erythromycin 83.33%.Due to wide scale resistance of the drugs used to treat UTI, choice of drugs in the treatment of UTI is quite narrow. In country like ours awareness for prevention of UTI should be encouraged among the community level as it affects all age groups. South East Asia Journal of Public Health Vol.7(2) 2017: 12-18